Feto-Maternal Outcomes In Teenage Pregnancy - Rajesh, Samhita; K, Vijayalakshmi (Journal of Neonatal Surgery, 2025)
Background: Teenage pregnancy is a significant public health issue, particularly in developing countries, due to its association with adverse maternal and neonatal outcomes. This study aimed to evaluate the feto-maternal outcomes of teenage pregnancies at Chettinad Hospital and Research Institute. Methods: A retrospective cross-sectional study was conducted from June 2022 to January 2025, involving 119 teenage pregnancies aged 13-19 years. Data on age, parity, gestational age, maternal outcomes, antenatal and postnatal complications, birth weight, APGAR scores, and neonatal complications were collected from hospital records. Descriptive statistics were used to analyze the data. Results: The majority of pregnancies occurred in the 18-19 years age group (59.4%), with 82.5% being primigravida. Preterm deliveries accounted for 32.4% of cases, while 64.9% were term deliveries. Vaginal deliveries (67.6%) were more common than cesarean deliveries (32.4%), with cephalopelvic disproportion (10.8%) being the leading indication for cesarean section. Anemia (40.5%) and pre-eclampsia (21.6%) were the most common antenatal complications. Postpartum hemorrhage (8.1%) was the most frequent postnatal complication. Low birth weight was observed in 40.5% of neonates, and 16.2% required NICU admission. Respiratory distress syndrome (10.8%) and neonatal jaundice (8.1%) were the most common neonatal complications. Conclusion: Teenage pregnancies are associated with significant maternal and neonatal risks, including high rates of anemia, pre-eclampsia, preterm delivery, and low birth weight. Targeted interventions, including nutritional support, early antenatal care, and specialized neonatal services, are essential to improve outcomes for teenage mothers and their infants. A multidisciplinary approach involving healthcare providers, educators, and social workers is crucial to address the challenges of teenage pregnancy effectively.